Functional reconstitution of beta-adrenergic receptors and the stimulatory GTP-binding protein of adenylate cyclase. - Pedersen, S E (1982)
A procedure for the functional reconstitution of beta-adrenergic receptors and the stimulatory guanine nucleotide-binding protein (G/F) of adenylate cyclase in phospholipid vesicles is described. beta-Adrenergic receptors were solubilized from turkey erythrocyte plasma membranes and reconstituted into phospholipid vesicles by the addition of dimyristoyl phosphatidylcholine and removal of detergent by gel filtration. This procedure restored the ability to bind [125I]iodohydroxybenzylpindolol and [3H]dihydroalprenolol. Purified rabbit hepatic G/F that was added to the receptor vesicles could be stably activated by guanosine 5'-[3-thio]triphosphate at a low rate, and this activation was increased up to 4-fold in the presence of beta-adrenergic agonists. This stimulation of the activation of G/F was specific for beta-adrenergic agonists and could be specifically blocked by beta-adrenergic antagonists. Stimulation was proportional to the concentration of vesicles containing active beta-adrenergic receptor. Under optimal conditions, 5 to 6 molecules of G/F were activated per receptor, indicating that catalytic activation of G/F by receptor was reconstituted.